2008
DOI: 10.1111/j.1610-0387.2008.06825_supp.x
|View full text |Cite
|
Sign up to set email alerts
|

Werden Zwangs‐ und Persönlichkeitsstörungen bei Berufsdermatosen ausreichend berücksichtigt? Eine Diskussion anhand von drei Fallbeispielen

Abstract: Hand dermatitis is relatively common in the general population. Among work-related diseases, it is the most common form of occupational skin disease. Irritant hand dermatitis is the most frequent type. Besides wet work and direct contact to irritating occupational substances frequent hand washing can damage the barrier function of the skin facilitating the manifestation of hand dermatitis that frequently occurs chronically. According to own observations the role of obsessive-compulsive washing as part of an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Mental factors can also significantly impact the course of skin diseases, including dermatoses of the hands [31–33]. About 50 % of patients with dermatoses of the hand are convinced that “stress” affects the course of their skin disease [31].…”
Section: Differential Diagnoses and Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Mental factors can also significantly impact the course of skin diseases, including dermatoses of the hands [31–33]. About 50 % of patients with dermatoses of the hand are convinced that “stress” affects the course of their skin disease [31].…”
Section: Differential Diagnoses and Clinical Featuresmentioning
confidence: 99%
“…In this study, it was also demonstrated that the subjective reaction to stress correlates with the severity of the skin disease, depression and the experience of significant life events [31]. In hand dermatoses or pruritus of the hands, compulsive disorders such as compulsive hand‐washing must be considered as well [32]. These patients are controlled by compulsive thoughts.…”
Section: Differential Diagnoses and Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations